(untitled) - Silberschatz, Abraham (Reading, Massachusett, 1994)
This is the most successful operating systems book on the market, with lifetime sales of well over 200,000 copies. In the fourth edition, this book enhances its reputation for clear coverage of the fundamental concepts which are the foundation of operating systems. The book has been revised to decrease coverage of older ideas, and expand discussion of new, common operating systems
Keywords: Hệ điều hành (Máy vi tính),Operating systems (Computers)